An Integrated Guidance Model For Pastor Candidates In Santo Vincetius Boarding High School Blitar - Widyanto, Rob Tri Budi; Sumaryanto, Totok; Budi Utomo, Cahyo (Educational Management, 2019)
Integrated guidance model between IQ, EQ and SQ are essential to produce the quality of next generation. Here, the author examines the Seminary of St. Vincent High School Blitar that has specificity in terms of an integrated development model of IQ, EQ and SQ. This study aims to gain a real picture of the integrated high school guidance model is based on stages of planning, organizing, implementation, and evaluation. This study used a qualitative approach with case study design. Techniques used to conduct the data such as interviews, observation and documentation. Analysis and data management is done by: data reduction, data presentation and verification of data. To ensure validation of the data it uses triangulation, namely: triangulation of data sources. The results of this study addressed that: 1) Development planning has been carried out based assessment company needed guidance. 2) The organization has done well through the establishment of organizational structure and establishment of authority and responsibility. 3) The implementation has been done procedurally by stipulation curriculum and budget amounts 4) evaluation has been carried out with good effective evaluation of the level of reaction, the rate of learning, behavioral level, and the level of impact.